Comparing the sensitivity and specificity of otoacoustic emission screeners in diagnosing noise-induced hearing loss from air conduction pure tone audiogram in a hearing conservation programme - Razali , Ailin; A. Rahman, Nor Azlina (2010)
One of the key components of hearing conservation programme is the yearly pure tone audiogram (PTA) obtained from workers who are at risk of developing noise-induced hearing loss from occupational noise exposure. Although it is the current gold-standard for assessing one’s hearing threshold, a number of limitations are associated with the PTA. It is not an objective test, it is time consuming, it needs trained technician and a sound-proof room (or at least a very quiet ambience) and it is deemed not sensitive enough to detect subtle changes in the cochlea due to early exposure to noise as it assesses the whole auditory pathway and not just the cochlea, where damage from noise mainly occur. A likely alternative would be otoacoustic emission (OAE), an objective test that measures the emission of outer hair cells which ideally would reflect early damages from sound, and takes only fraction of the time to do PTA to complete. Our objective is to see whether screening OAE can be used instead of PTA for early detection of NIHL. A total of 72 workers from a quarry in Kuantan recently underwent PTA, TEOAE, DPOAE and DDPOAE. The association between PTA and OAE (right and left ear) was tested using McNemar’s test and the proportion between the pass and refer cases of OAE and PTA findings was noted to be significant. We will then report on the sensitivity and specificity of different types of OAE as stated above when compared to PTA as gold-standard.